Whole Gene Deletion of EBF3 Supporting Haploinsufficiency of This Gene as a Mechanism of Neurodevelopmental Disease - Lopes, Fátima; Soares, Gabriela; Gonçalves-Rocha, Miguel; Pinto-Basto, Jorge; Maciel, Patrícia (Frontiers in Genetics, 2017)
Mutations in early B cell factor 3 (EBF3) were recently described in patients with a neurodevelopmental disorder that includes developmental delay/intellectual disability, ataxia, hypotonia, speech impairment, strabismus, genitourinary abnormalities and mild facial dysmorphisms. Several large 10q terminal and interstitial deletions affecting many genes and including EBF3 have been described in the literature. However, small deletions (<1MB) affecting almost exclusively EBF3 are not commonly reported. We performed array comparative genomic hybridization (aCGH) (Agilent 180K) and quantitative PCR analysis in a female patient with intellectual disability. A clinical comparison between our patient and overlapping cases reported in the literature was also made. The patient carries a de novo 600Kb deletion at 10q26.3 affecting the MGMT, EBF3 and GLRX genes. The patient has severe intellectual disability, language impairment, conductive hearing loss, hypotonia, vision alterations, triangular face, short stature and behavior problems. This presentation overlaps that reported for patients carrying EBF3 heterozygous point mutations, as well as literature reports of patients carrying large 10qter deletions. Our results and the literature review suggest that EBF3 haploinsufficiency is a key contributor to the common aspects of the phenotype presented by patients bearing point mutations and indels in this gene, given that deletions affecting the entire gene (alone or in addition to other genes) are causative of a similar syndrome, including intellectual disability with associated neurological symptoms and particular facial dysmorphisms.